Depression subtypes, suicidality, and healthcare costs in older adults: results from a naturalistic study - Conejero, Ismael; Porras-Segovia, Alejandro; Albarracín-García, Lucía; Barrigón, María Luisa; Lopez-Castroman, Jorge; Courtet, Philippe; Baca-Garcia, Enrique (Frontiers in Psychiatry, 2025)
IntroductionThe burden of depression is increasing worldwide, particularly in older populations. While the impact of depressive disorders on suicide in later life has been clearly identified, less is known about the role of their subtypes and their costs in the elderly.ObjectivesWe aimed to describe the sociodemographic and clinical characteristics associated with the depression subtypes and suicidality, and their related healthcare costs in older adults receiving mental healthcare.MethodologyThe study was carried out across four psychiatry departments in Madrid, Spain. Adults aged over 60 years were included if they attended the psychiatric inpatient or outpatient services and were diagnosed with Major Depressive Disorder (MDD), recurrent depressive disorder, bipolar depression, or dysthymia. Sociodemographic data and diagnoses according to the International Classification of Diseases, 10th edition were obtained from electronic health records. Lifetime suicidal history, suicidal ideation and suicide attempts in the previous month were identified using the Columbia Suicide Severity Rating Scale (CSSRS). Mean healthcare costs were calculated over one year.ResultsN=2868 patients were included in the analysis. Of these, 550 were assessed with the CSSR. The mean age of the sample was 70.05 years and 75.9% of the patients were women (N=2177). Of the patients assessed with the CSSRS (N=550), 83.2% (N=458) reported suicidal ideation, and 7.3% (N=40) had attempted suicide in the previous month. Psychiatric healthcare costs over the follow-up differed between the depression subtypes (Eta-squared 0.003 CI [0.000 - 0.008]; p<0.001). They were significantly higher in patients diagnosed with bipolar depression, than in those diagnosed with dysthymia (p=0.026), but did not differ from those bearing MDD (p= 0.775) or recurrent depressive disorder (p= 0.129). Recent suicide attempters had a more frequent lifetime history of suicide attempt (OR= 8.434). Suicide attempts were more frequent in individuals aged 71-80 years (OR= 3.433) or over 80 years (OR= 3.322), and in patients with recurrent depressive disorders (OR= 3.529).ConclusionPsychiatric healthcare costs differed between depression subtypes, with a small effect. Furthermore, older age, a diagnosis of recurrent depression, and a history of suicide attempts increased the risk of suicide. Health policies should target these populations to improve mental health outcomes in the older adults.